Is Education Neglected in Natural Resources-Rich Countries? : An Intergenerational Approach in Africa - Atsebi, Jean-Marc (IMF Working Papers; Working Paper ;, 2022)
The literature on the effects of natural resources on education is mixed and inconclusive. In this paper, we adopt an innovative approach by exploring the effects of mineral discoveries and productions on intergenerational educational mobility (IM), linking parents to the children education levels for more than 14 million individuals across 28 African countries and 2,890 districts. We find that mineral discoveries and productions positively affect educational IM for primary education in Africa for individuals exposed to the mineral sites and living in districts with discoveries. Specifically, the probability of upward primary IM increases by 2.7 percentage points (pp.) following mineral discoveries and 6.7 pp. following mineral productions. Downward primary IM decreases by 1.2 pp. following both mineral discoveries and productions. These positive effects are increasing for individuals born later after discoveries and productions, for males, and individuals living in the urban area. However, no significant effects are found for secondary and tertiary educational IM. Finally, we explore the income and returns to education channels through which mineral discoveries and productions affect educational IM.